Update of human and mouse matrix metalloproteinase families - Jackson Brian C; Nebert Daniel W; Vasiliou Vasilis (Human Genomics, 2010)
Abstract Matrix metalloproteinases (MMPs) are a family of zinc proteases that degrade most of the components of the extracellular matrix (ECM). MMPs also have a number of non-traditional roles in processing factors related to cell growth/proliferation, inflammation and more. There are 23 human MMPs and 23 mouse MMPs, most of which share orthology among most vertebrates; other examples have been found in invertebrates and plants. MMPs are named in order of discovery, but also have been grouped by domain structure or by phylogenetic analysis. MMPs are multi-domain proteins which generally contain a signal sequence; propeptide (which keeps the protein inactive until cleaved); catalytic domain; and a hemopexin-like domain (which provides substrate specificity). MMPs are thought to play a role in many disease states, including arthritis, vascular disease, lung injury, wound repair, cancer and various neurodegenerative disorders. Although there has been much clinical interest in MMP inhibitors (MMPIs), few trials have been successful -- often due to the broad nature of inhibition and the complex role of different MMPs in a given disease state.